Turban Pin Inhalation Syndrome with Unusually Mobile Pin from Series of Radiographs - Win Tin; Firdaus Hayati; Rajesh Muniandy; Constance Liew Sat Lin; Christopher Lim; Aung Mra; Khin Nyein Yin (2020)
Foreign Bodies (FB) dislodges are common in the ear, nose and throat especially among infants and children. Occasionally, they can accidentally be ended up in the bronchus as well. We describe a 13-year-old girl with accidental ingestion of a scarf needle pin after she was slapped on the back while biting the pin. Chest radiograph had confirmed the diagnosis of pin ingestion which is consistent with turban pin inhalation syndrome. In view of logistic and specialty issues, she was transferred to another tertiary hospital for further intervention. A series of chest radiograph showed a migratory metallic FB in different locations in the airway, which was considered as an extreme rarity. We discuss this rare entity with literature review of FB aspiration in general.